Dynamic, continuous multitasking training leads to task-specific improvements but does not transfer across action selection tasks. (December 2017) - Bender, Angela; Filmer, Hannah; Naughtin, Claire; Dux, Paul
Abstract The ability to perform multiple tasks concurrently is an ever-increasing requirement in our information-rich world. Despite this, multitasking typically compromises performance due to the processing limitations associated with cognitive control and decision-making. While intensive dual-task training is known to improve multitasking performance, only limited evidence suggests that training-related performance benefits can transfer to untrained tasks that share overlapping processes. In the real world, however, coordinating and selecting several responses within close temporal proximity will often occur in high-interference environments. Over the last decade, there have been notable reports that training on video action games that require dynamic multitasking in a demanding environment can lead to transfer effects on aspects of cognition such as attention and working memory. Here, we asked whether continuous and dynamic multitasking training extends benefits to tasks that are theoretically related to the trained tasks. To examine this issue, we asked a group of participants to train on a combined continuous visuomotor tracking task and a perceptual discrimination task for six sessions, while an active control group practiced the component tasks in isolation. A battery of tests measuring response selection, response inhibition, and spatial attention was administered before and immediately after training to investigate transfer. Multitasking training resulted in substantial, task-specific gains in dual-task ability, but there was no evidence that these benefits generalized to other action control tasks. The findings suggest that training on a combined visuomotor tracking and discrimination task results in task-specific benefits but provides no additional value for untrained action selection tasks. Cognition: multitasking training boosts task-specific skills only Training on a dynamic multitasking game leads to task-specific improvements but this performance gain does not transfer to novel tasks. Bender and colleagues from the University of Queensland, Australia, had one group of human participants train on a combined visuomotor tracking and shape discrimination task over several days, while another group trained on the two tasks in isolation (active control group). Following training, multitasking performance selectively improved for the multitasking group and not for the active control group. Critically, this training-related benefit did not generalize to a wide range of cognitive tasks that are theoretically linked to the current dual-task paradigm, indicating that repeated exposure to two concurrent tasks induces the learning of task-specific skills so that coordination between two specific tasks can be implemented more efficiently.